KETERAMPILAN PEMECAHAN MASALAH SOAL CERITA PERKALIAN BILANGAN CACAH DITINJAU DARI GAYA BELAJAR - Devita Wahyu; I Ketut Suastika; Dyah Triwahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze problem-solving skills in multiplication story problems from the perspective of learning styles. The research method used is descriptive qualitative, with three fourth-grade students who have visual, auditory, and kinesthetic learning styles as subjects. Data were collected through questionnaires, story problems tests, and interviews, and analyzed based on four indicators of Polya's theory: understanding the problem, planning a solution, implementing the plan, and drawing conclusions. The results showed that visual learners were able to meet all indicators, auditory learners only completed two stages, and kinesthetic learners only one stage. These differences indicate that learning styles influence students' problem-solving skills. This is important because, to date, classroom teaching approaches often do not consider individual learning styles, leading many students to struggle with story problems. Therefore, teachers need to adapt teaching methods and media to students' learning style characteristics and help them identify the most suitable learning approach to enhance the effectiveness of mathematics learning.